Alternating copolymerization of functionalized silica nanoparticles. (28th February 2019) - Fukuda, Keisuke; Yoshitake, Hideaki
Abstract: In order to alternatively "polymerize" two kinds of nanoparticles, monodisperse silica particles with a diameter of 20 nm and those with diameters of 100 nm were functionalized with 3-glycidyloxypropyltrimethoxysilane and N-(6-aminohexyl)aminopropyltrimethoxysilane, respectively, and these particles were made to react with each other by mortar-and-pestle mixing under ambient conditions to induce a copolymerization of the two different kinds of nanoparticles. In the Raman spectrum after the mixing, the bands attributed to α-amino alcohol bonds were observed, implying that the conditions were sufficient to bring about reactions between the epoxy ring on 20 nm-particles and the amine on 100 nm-particles. The porous structure was different from that of the mixture of non-functionalized nanoparticles, as unveiled by nitrogen adsorption-desorption experiments. The pore volume of the solid increased considerably from those of the agglomerates precursor silica nanoparticles. The positioning of two kinds of particles was revealed by the observation of SEM images; 20 nm-particles are juxtaposed with a 100 nm-particle and vice versa. However, using nanoparticles with a diameter of 10 nm, the porous structure was not much different from that of the mixture of non-functionalized nanoparticles, implying that redispersion hardly occurs for such small nanoparticles even with functionalization. The adsorption capacity for arsenate of the porous solid is almost equal to the amount of amino groups in the solid, which is demonstrated by Langmuir isotherm analysis. The plot has a fold at a surface coverage of 0.25 for which a change in the mode of adsorption is implied. Graphical abstract: Image 1 Highlights: Glycidyloxy- and aminoalkyl-functionalized particles were copolymerized by mechanical mixing. This is a novel method for the preparation of highly mesoporous solids. The pore volume of the solid is much increased from that of the precursor silica nanoparticles. Distinctive characteristics were found in the adsorption of arsenate on this mesoporous solid.